Over 300 Radiation Caries Papers: Reflections From the Rearview Mirror - Pedroso, Caique Mariano; Migliorati, Cesar Augusto; Epstein, Joel B.; Ribeiro, Ana Carolina Prado; Brandão, Thaís Bianca; Lopes, Márcio Ajudarte; de Goes, Mário Fernando; Santos-Silva, Alan Roger (Frontiers in Oral Health, 2022)
Radiation caries (RC) is an aggressive oral toxicity in head and neck cancer survivors, which develops 6 to 12 months after head and neck radiotherapy. It initially affects the tooth cervical/incisal surfaces, and if not promptly diagnosed/managed, progresses to dental crown amputation and risk of osteoradionecrosis. It results from a multidimensional cluster of treatment-induced oral symptoms, including hyposalivation, dietary changes, and oral hygiene impairment. Although recognized as a frequent complication of radiotherapy and extensively assessed by a myriad of retrospective, in vitro, and in situ studies, RC patients are still orphans of clinically validated methods for risk prediction, prevention, and treatment of early lesions. This review provides a historical overview of science-based concepts regarding RC pathogenesis and treatment, emphasizing the growing demand for interventional clinical studies (randomized trials).